PERAN PENGGUNAAN MEDIA SOSIAL DALAM PEMBENTUKAN KARAKTER MAHASISWA MANAJEMEN PENDIDIKAN ISLAM UIN ALAUDDIN MAKASSAR - Rahim, Sri Mulyani; Syam, Nur Hikmah; Murdani, Indra; Amiruddin, Idris (Educational Leadership: Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the role of social media in shaping the character of students in the Islamic Education Management (MPI) Study Program at UIN Alauddin Makassar. A qualitative descriptive approach was employed to explore students’ subjective experiences in using social media. Data were collected through in-depth interviews with four students as primary data, supported by literature studies including books and scholarly journal articles as secondary data. Data were analyzed using thematic analysis through data presentation and conclusion drawing. The findings indicate that social media plays a significant role in shaping students’ self-perceptions, particularly related to academic achievement, lifestyle, physical appearance, and religious activities displayed online. Social media use also generates anxiety, self-doubt, idealized self-presentation, and motivation for self-improvement. This study concludes that social media significantly influences the identity formation of MPI students in both online and offline interactions, highlighting the importance of digital literacy guidance in supporting healthy character development among university students.